Analisis kemampuan literasi matematika siswa dalam menyelesaikan permasalahan asesmen kompetensi minimum (AKM) - Sari, Rully Devita; Lusiana, Restu; Susanti, Vera Dewi (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2023)
This study aims to analyze the mathematical literacy ability of SMK students in solving the minimum competency assessment (AKM) problem in the opportunity material in terms of mathematical cognitive ability. The subjects in this study were students of class XI MM 2 SMKN 1 Wonoasri with high, medium and low mathematical cognitive abilities of 1 subject each. This type of research is qualitative research. Data collection techniques based on the results of cognitive tests, AKM and interviews. Data validity techniques with engineering triangulation. Data analysis is carried out by reducing, presenting and verifying data and drawing conclusions. The conclusion of the study is that the cognitive subjects of high mathematics at level 1 write down information in detail, level 2 uses coding and solves problems by dividing them, level 3 solves problems by simplification and multiplication. The cognitive subject of mathematics is at level 1 writing down information briefly, level 2 uses coding and solves problems by simplification, level 3 solves problems by simplification and division. The cognitive subject of low mathematics at level 1 writes down the information briefly, level 2 problem solving performed has not been completed, level 3 problem solving is not in accordance with the command.